RISK FACTORS FOR BODY REGION SPECIFIC INJURIES IN SKIERS AND SNOWBOARDERS. Issue 7 (11th March 2014) - Romanow, NTR; Pfister, K; Rowe, BH; Emery, CA; Meeuwisse, WH; Nettel-Aguirre, A; Goulet, C; Russell, K; McRae, A; Lang, E; Hagel, BE
Abstract : Background: Little is known about risk factors (e.g., wrist guards, binding adjustment, equipment ownership) for body region specific skiing/snowboarding injuries. Objective: Identify risk factors for body region specific injuries and severe injuries in skiers/snowboarders. Design: Case-control study using emergency department (ED) interviews, ski patrol Accident Report Forms (ARF), and ski area interviews. Severe injury cases presented to the ED. Non-severe injury cases presented to the ski patrol. Controls were uninjured skiers/snowboarders. Setting: An urban ski area and 2 EDs in Alberta, Canada. Participants: Injured skiers/snowboarders who saw the ski patrol (n=552) or went to one of the study EDs (n=192). Controls were interviewed at the ski area (n=914). Risk factor assessment: Risk factor data were collected by interview and from ARFs. Injury outcomes were determined from the ED chart or ARF. Main outcome measurements: Body region categories were: lower extremities, upper extremities, trunk, and head/neck. Odds ratios (OR) with 95% confidence intervals (CI) were calculated for each body region by case group. Intrinsic risk factors (age, sex, activity, ability) will be included in the models. Results: Preliminary results for non-severe cases indicate that the odds of injury for all body regions were lower for those 12+ years old compared with younger participants (OR range 0.07; 95% CI 0.04–0.11 to 0.42; 95% CI 0.24–0.73) and higher for beginners (OR range 1.79; 95% CI 1.01–3.15 to 4.97; 95% CI 2.97–8.32). Overcast weather reduced the odds of any injury (OR range 0.06; 95% CI 0.02–0.18 to 0.44; 95% CI 0.2–0.98), as did increased run difficulty (OR range 0.06; 95% CI 0.02–0.17 to 0.19; 95% CI 0.0–0.54). Skiers had lower odds of upper body injury (ARF OR 0.27; 95% CI 0.2–0.38 & ED OR 0.33; 95% CI 0.21–0.51) compared with snowboarders. Conclusions: These results will inform the development of an injury prevention program for skiers/snowboarders targeting modifiable risk factors.